Poles in the Dutch Cape Colony 1652-1814 - Kowalski, Mariusz (Werkwinkel, 2015)
The contribution of Poles to the colonisation and development of the Dutch Cape Colony is not commonly known. Yet, Poles have been appearing in this colony since its very inception (1652). During the entire period considered here the presence of Poles was the result of the strong economic ties between Poland and the Netherlands. At the end of this period there was an increase in their share, in connection with the presence of numerous alien military units on the territory of the Colony, because of Poles having served in these units. Numerous newcomers from Poland settled in South Africa for good, established families, and their progeny made up part of the local society. The evidence of this phenomenon is provided by the present-day Afrikaner families of, for instance, Drotsky, Kitshoff, Kolesky, Latsky, Masuriek, Troskie, Zowitsky, and others. A quite superficial estimation implies that the settlers coming from Poland could make up a bit over 1% of the ancestors of the present-day Afrikaners. Poles would also participate in the pioneering undertakings within the far-off fringes of the Colony, including the robbery-and-trade expedition of 1702.